Impact of Agricultural Insecticide Vapona on a Freshwater Catfish Heteropneustes Fossilis: A Toxicity Study - Prasad, Nayan K.; Sahani, Suresh Kumar (Darul Yasin Al Sys, 2024)
This study investigates the critical toxicity of Vapona in the air-breathing freshwater catfish, Heteropneustes fossilis (Bloch). The LC50 values (median lethal concentration) were determined using a static bioassay method over 24, 48, 72, and 96-hour exposure periods. The LC50 values for 24, 48, 72, and 96 hours of Vapona were found to be 400, 378, 320, and 275 ppm, respectively. An increased mucus secretion was observed at higher concentrations, suggesting a physiological response to the toxicant. The potential causes of mortality in the fish were also analyzed and discussed.